2015
DOI: 10.5424/sjar/2015131-6145
|View full text |Cite
|
Sign up to set email alerts
|

Sewage sludge use in bioenergy production. A case study of its effects on soil properties under Cynara cardunculus L. cultivation

Abstract: Energy crops cultivation is expected to further increase, which represents an opportunity to establish synergies able to enhance key environmental components (i.e. soil). To reach this benefits crop management is crucial and should be properly assessed. The aim of this work is to provide an insight on the effects of sewage sludge compost (SSC) on soil properties, when this material is applied as basal dressing for the cultivation of a Mediterranean energy crop (Cynara cardunculus L.). A 3-years trial (2008/201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…The results revealed the OIF treatment was more effective for soil acidification, organic carbon accumulation and fertility improvement, which indicated that it could be an important fertilization technique to improve the soil fertility quality of Paulownia plantations. Long-term application of organic fertilizers contributed to the accumulation of SOM, thereby improving soil fertility, which is consistent with other findings (Lag-Brotons et al, 2015). Our results also revealed that fertilization could significantly increase soil enzyme activity and microbial biomass in the two different-aged Paulownia plantations, especially soil UA, CA, APA, MBC and MBN under the OIF treatment.…”
Section: Effects Of Different Fertilization On Soil Chemical Properties Of Paulownia Plantationsupporting
confidence: 91%
“…The results revealed the OIF treatment was more effective for soil acidification, organic carbon accumulation and fertility improvement, which indicated that it could be an important fertilization technique to improve the soil fertility quality of Paulownia plantations. Long-term application of organic fertilizers contributed to the accumulation of SOM, thereby improving soil fertility, which is consistent with other findings (Lag-Brotons et al, 2015). Our results also revealed that fertilization could significantly increase soil enzyme activity and microbial biomass in the two different-aged Paulownia plantations, especially soil UA, CA, APA, MBC and MBN under the OIF treatment.…”
Section: Effects Of Different Fertilization On Soil Chemical Properties Of Paulownia Plantationsupporting
confidence: 91%
“…For general purposes, the use of organic amendments in soil rehabilitation and restoration has the main objective of adding and increasing the organic matter and favoring the availability of nutrients for plants (Lag-Brotons et al, 2015). Moreover, the organic amendments influence the structure and physical soil properties, as many works have demonstrated (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Energy crops cultivation aims to maximize biomass feedstock obtained per unit of area, minimize production inputs, and avoid land competition with food crops (Lag-Brotons et al, 2015). In addition, environmental co-benefits can be achieved through the sustainable cultivation of energy crops, such as the protection of soil, the increase in terrestrial carbon sinks and reservoirs and the reduction of greenhouse gases emissions (Sims et al, 2006).…”
Section: Introductionmentioning
confidence: 99%